Pathological Clotting and Deep Vein Thrombosis in Patients with HIV - Jackson, Brandon S.; Pretorius, Etheresia (Seminars in Thrombosis and Hemostasis, 2019)
The number of people infected with human immunodeficiency virus (HIV) is rapidly increasing and the majority of those infected are living in sub-Saharan Africa. Some hallmarks of HIV are inflammation and upregulation of inflammatory markers. A pathological coagulation system may accompany these inflammatory changes and potentially result in venous thromboembolism such as a deep vein thrombosis (DVT). In this review, the authors describe the inflammatory profile in HIV, the treatment regimens currently in place in South Africa, and in particular how HIV affects the hematological system, with specific focus on platelets, red blood cells (RBCs; erythrocytes), and fibrin(ogen). They also discuss the presence of DVT in HIV, focus on screening tests, and suggest a more proactive approach to track the inflammatory profile of HIV patients, by specifically using parameters that might point to pathological coagulation; these should involve platelet, RBC, and fibrin(ogen) analysis. They conclude by suggesting that including coagulation function tests to study the effect of treatment interventions would improve outcomes in these individuals, as it could help in the diagnosis of thromboembolic disease. Furthermore, this approach could streamline treatment strategies due to improved monitoring. A better understanding of hypercoagulability of HIV-infected patients is therefore urgently needed. In conclusion, the authors suggest a panel of pathology tests that should be considered as standard procedures when HIV is present.
Keywords: human immunodeficiency virus; deep vein thrombosis; antiretroviral medication; inflammation; coagulation